Cardiovascular Imaging Techniques in Systemic Rheumatic Diseases - Atzeni, Fabiola; Corda, Marco; Gianturco, Luigi; Porcu, Maurizio; Sarzi-Puttini, Piercarlo; Turiel, Maurizio (Frontiers in Medicine, 2018)
The risk of cardiovascular (CV) events and mortality is significantly higher in patients with systemic rheumatic diseases than in the general population. Although CV involvement in such patients is highly heterogeneous and may affect various structures of the heart, it can now be diagnosed earlier and promptly treated. Various types of assessments are employed for the evaluation of CV risk such as transthoracic or transesophageal echocardiography, magnetic resonance imaging (MRI), and computed tomography (CT) to investigate valve abnormalities, pericardial disease, and ventricular wall motion defects. The diameter of coronary arteries can be assessed using invasive quantitative coronarography or intravascular ultrasound, and coronary flow reserve can be assessed using non-invasive transesophageal or transthoracic ultrasonography (US), MRI, CT, or positron emission tomography (PET) after endothelium-dependent vasodilation. Finally, peripheral circulation can be measured invasively using strain-gauge plethysmography in an arm after the arterial infusion of an endothelium-dependent vasodilator or non-invasively by means of US or MRI measurements of flow-mediated vasodilation of the brachial artery. All of the above are reliable methods of investigating CV involvement, but more recently, introduced use of speckle tracking echocardiography and 3-dimensional US are diagnostically more accurate.